2014
DOI: 10.1007/978-3-319-11203-9_15
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Cloud-Based Revocable Identity-Based Proxy Re-encryption Scheme for Public Clouds Data Sharing

Abstract: Identity-based encryption (IBE) eliminates the necessity of having a costly certificate verification process. However, revocation remains as a daunting task in terms of ciphertext update and key update phases. In this paper, we provide an affirmative solution to solve the efficiency problem incurred by revocation. We propose the first cloud-based revocable identity-based proxy re-encryption (CR-IB-PRE) scheme that supports user revocation but also delegation of decryption rights. No matter a user is revoked or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
91
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(91 citation statements)
references
References 34 publications
0
91
0
Order By: Relevance
“…In this paper, we showed that the CR-IB-PRE scheme [4] is vulnerable to collusion attacks whereby a non-revoked user's private key is revealed. How to construct the CR-IB-PRE scheme with a constant number of private key and update key elements remains an open problem.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this paper, we showed that the CR-IB-PRE scheme [4] is vulnerable to collusion attacks whereby a non-revoked user's private key is revealed. How to construct the CR-IB-PRE scheme with a constant number of private key and update key elements remains an open problem.…”
Section: Resultsmentioning
confidence: 99%
“…The security model of CR-IB-PRE was introduced by Liang et al [4]. In this security model, the update token query takes as input identity ID and time T .…”
Section: Security Model Of the Cr-ib-pre Schemementioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, by using the aforementioned revocation technique, Libertand Vergnaud [9] proposed an adaptively secure RIBE scheme based on a variant of Water's IBE scheme [10] Chenet al [11]. Constructed an RIBE scheme, from lattices.…”
Section: Literature Surveymentioning
confidence: 99%
“…In PRE scheme, the proxy does not know the secret key of Alice or Bob, and also does not know the plaintext during the conversion. PRE schemes have many applications such as digital rights management (DRM), distributed storage, encrypted email forwarding, and law enforcement [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%